Natural resource economics : notes and problems - Conrad, Jon M. (Cambridge University Press, 1987)
This book is divided into five parts: Resource allocation and Optimization; Renewable Resources; Nonrenewable Resources; Environmental Management; and Stochastic Resource Models.